DESIGN TOOL ROOM DOOR ALARM ON AT89C51 MICROCONTROLLER - M. Piqih Armansyah; Indrianto. Skom. MT Indrianto. Skom. MT (Jurnal Sistem Komputer, 2007)
In general, this door design tool can be applied easily. Optocoupler sensor responsetowards the open door can be detected properly. So also with the performance of LEDand buzzer as a timely warning when the sensor was detected.Specifically, the program for running the door alarm was spelled out successfully,because the microcontroller program commands can be processed and properlyinstructed.